Low‐Cost, Facile, and Scalable Manufacturing of Capacitive Sensors for Soft Systems. Issue 9 (24th July 2017) - White, Edward L.; Yuen, Michelle C.; Case, Jennifer C.; Kramer, Rebecca K.
Abstract : In the field of soft robotics there is a need for robust and reliable large‐deformation strain sensing. Further, the field needs a way to produce such sensors in large quantities and at low cost. Toward these goals, the fabrication of highly stretchable capacitive strain sensors made from conductive elastomer composites is described here. Two novel methods of manufacturing these sensors directly onto a fabric substrate are developed: direct writing of elastomer using an extrusion process and screen printing of elastomer patterns. The effect of material processing parameters on the parameters of the finished composite films is studied and it is determined that the process is robust to a wide range of variations. The performance of sensors produced on fabric substrates is shown to be similar between the two fabrication processes. Further, the sensors are highly deformable with consistent performance up to 250% strain, and are reliable, with no changes in performance observed at 1000 cycles. It is also demonstrated that the sensors continue to perform with reduced gauge factors up to 100 000 cycles. For comparison, free‐standing capacitive sensors are also produced with the same materials and it is shown that these devices are equally stable and robust. In conclusion, the fabrication process demonstrated here is robust to process variations and is capable of producing sensors directly on fabric substrates, which facilitates the production of large arrays of sensors without the need for an additional assembly step. Abstract : Highly deformable strain gauges are fabricated directly onto fabric substrates using screen printing and direct writing. The resulting devices are robust and continue to operate after 100 000 cycles, and up to 250% strain. The variations in processing conditions, from conductive composite to deposition, are shown to have limited effect on sensor performance.